Comparative Effectiveness and Safety of High-Intensity Focused Ultrasound for Uterine Fibroids: A Systematic Review and Meta-Analysis - Wang, Yi; Geng, Jinsong; Bao, Haini; Dong, Jiancheng; Shi, Jianwei; Xi, Qinghua (Frontiers in Oncology, 2021)
Background: Uterine fibroids are common benign tumors among premenopausal women. High- intensity focused ultrasound (HIFU) is an emerging non-invasive intervention which uses the high-intensity ultrasound waves from ultrasound probes to focus on the targeted fibroids. However, the efficacy of HIFU in comparison with that of other common treatment types in clinical procedure remains unclear. Objective: To investigate the comparative effectiveness and safety of HIFU with other techniques which have been widely used in clinical settings. Methods: We searched the Cochrane Central Register of Controlled Trials, PubMed, EMBASE, Cumulative Index to Nursing & Allied Health Literature, Web of Science, ProQuest Nursing & Allied Health Database, and three Chinese academic databases, including randomized controlled trials (RCTs), non-RCTs, and cohort studies. The primary outcome was the rate of re-intervention, and the GRADE approach was used to interpret the findings. Results: About 18 studies met the inclusion criteria. HIFU was associated with an increased risk of re-intervention rate in comparison with myomectomy (MYO) [pooled odds ratio (OR): 4.05, 95% confidence interval (CI): 1.82–8.9]. The results favored HIFU in comparison with hysterectomy (HYS) on the change of follicle-stimulating hormone [pooled mean difference (MD): −7.95, 95% CI: −8.92–6.98), luteinizing hormone (MD: −4.38, 95% CI: −5.17−3.59), and estradiol (pooled MD: 43.82, 95% CI: 36.92–50.72)]. HIFU had a shorter duration of hospital stay in comparison with MYO (pooled MD: −4.70, 95% CI: −7.46−1.94, p < 0.01). It had a lower incidence of fever (pooled OR: 0.15, 95% CI: 0.06–0.39, p < 0.01) and a lower incidence of major adverse events (pooled OR: 0.04, 95% CI: 0.00–0.30, p < 0.01) in comparison with HYS. Conclusions: High-intensity focused ultrasound may help maintain feminity and shorten the duration of hospital stay. High-quality clinical studies with a large sample size, a long-term follow-up, and the newest HIFU treatment protocol for evaluating the re-intervention rate are suggested to be carried out. Clinical decision should be based on the specific situation of the patients and individual values.